The cultivation of Ulva lactuca (chlorophyta) in an integrated aquaculture system, for the production of abalone feed and the bioremediation of aquaculture effluent - Robertson-Andersson, Deborah (Department of Biological Sciences, 2023)
Significant effort has been put into the development of cost-effective abalone cultivation systems in South Africa, but the limited availability of suitable seaweed for abalone food is an obstacle to future development. The aim of this study was to investigate whether land-based integrated aquaculture (tank cultivation) and seaweed culture using Ulva lactuca in aquaculture effluent was feasible. This study was carried out at two abalone farms: Danger Point (I & J) (140 km east of Cape Town) and Jacobsbaai (JSP) (120 km north of Cape Town, South Africa). Both farms want to supplement the abalone feed with Ulva and investigate its potential for recirculation. Ulva is one of the simplest seaweeds to cultivate as it grows vegetatively. It would have a further benefit in its capacity to absorb nutrients and thus improve water quality of the aquaculture effluent. Results show that abalone effluent medium alone is insufficient for seaweed cultivation. Turbot effluent media has far more nutrients for seaweed but turbidity due to incomplete turbot feed pellet assimilation could be a problem. The most effective cultivation media on both farms is a fertilized effluent growth medium. This study established that water exchange rates are important in assuring an optimum nutrient supply for the seaweed. At high water exchange rates (20 Volume Exchanges (VE).d ·1), Specific Growth Rate (SGR) in turbot and seawater treatments were not significantly different despite a significant difference in water nutrient concentration. Maximum nutrient removal occurs at both 12 and 20 volume exchanges per day, using a stocking density of 3 kgm·2 on both farms. Approximately 70 % of the ammonium is removed during the day and 60 % at night at JSP in both turbot and abalone treatments, while at I & J in the abalone treatments, 90 % and 80 % of the ammonium is removed during the day and night respectively. The diel fluctuation in dissolved oxygen is above critical levels (6 mg.I) for abalone respiration at night, thus indicating that direct recirculation is possible. The seaweeds grown at a high water exchange rate at JSP were all phosphate limited except in winter, when background phosphate concentrations increased. Thus, fertilizers like Maxiphos can benefit the alga, especially if the phosphate ratio were to be increased in summer. Maintaining a pH below 9 is important in maintaining seaweed health and should become an integral part of the farm management protocol. Myrionema strangulans is an epiphyte newly recorded for South Africa during this project and has potentially devastating effects for culture of Ulva. Pulse fertilization of culture tanks combined with seasonal shading (late September to early February) using 20 % shade cloth controls epiphytic and fouling algal growth, particularly Myrionema. Shading also improves thallus condition, increases tissue nitrogen and decreases pH. Shading with a 50 % shade cloth however, has a significant reduction on uptake of ammonium and phosphate by the seaweed as well as decreasing the SGR and resulting in a species dominace switch from Ulva lactuca to Ulva capensis. There is a decrease in SGR when scaling up tank sizes, but this decrease can be optimized by cultivating the alga in pulse fertilized effluent water. Growing Ulva in effluent media increases its tissue nitrogen and thus protein content, increasing it above levels found in nature (average protein content in turbot= 49.8 %) and improving it as a source of protein for cultured abalone. A consistent relationship between tissue nitrogen and thallus colour was determined and can be used by mariculture farmers to assess the nutrient quality of Ulva as a food source for abalone which has important benefits for Ulva aquaculture. On the I & J farm the chosen stocking density (2 kg.m"2) produced maximum SGR and yields. At JSP the chosen stocking density {2 kg.m"2) was too high and a stocking density of 1 kg.m·2 would have optimized SGR. Seasonal effects on stocking density were not investigated. Addition of Kelpak ® concentration (commercial kelp extract) of 1: 2 500 pulse fed once a week, increases SGR. This study has shown that Kelpak® in addition to fertilizer may have commercial potential in the seaweed mariculture industry. These results confirm that Ulva is exceptionally suitable for intensive culture in different types of nutrient loaded water, and that its cultivation on an abalone farm could have significant economic benefits. For example, a 50 ton abalone farm feeding protein enriched Ulva could decrease the production time from 5 years to 3.6 year which equates to a savings of between R 800 000 - R1 300 000.